Anti-inflammatory activity of Echium amoenum extract on macrophages mediated by inhibition of inflammatory mediators and cytokines expression - Najmeh Naseri (Research in Pharmaceutical Sciences, 2018)
Echium amoenum (Boraginaceae) is an important remedy used for various illnesses. In this study, we investigated the anti-inflammatory effects of E. amoenum in the J774.1A macrophage cell line. We prepared ethyl acetate, dichloromethane and hexane extracts from E. amoenum flowers and examined their possible cytotoxic effects using MTT assay. Lipopolysaccharide (LPS)-stimulated macrophages were treated with the extracts after which we measured nitric oxide (NO) production by Griess method. Inducible NO synthase (iNOS), cyclooxygenase-2 (COX2), tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6 gene expressions were examined by real time-PCR. IL-1β and IL-6 cytokine levels were measured by enzyme-linked immunosorbent assay (ELISA). The hexane extract with a half maximal inhibitory concentration (IC50) of 39.8 μg/mL most effectively reduced NO production. Real time-PCR analysis indicated reduced levels of iNOS ((0.05 ± 0.006 relative fold change (RFC)) and COX2 (0.06 ± 0.002 RFC) gene expressions with the 100 μg/mL hexane extract (P < 0.001). IL1-β, TNF-α, and IL-6 gene expression levels decreased at all concentrations of the extract (less than ≈ 0.28 RFC). Treatment of LPS-stimulated cells with 100 μg/mL of the extract reduced IL-1β secretion to 27.9 ± 0.21 pg/mL and IL-6 to 555 ± 166 pg/mL. In conclusion, E. amoenum hexane extract showed the greatest reduction in macrophage NO secretion compared to other extracts. This extract could modulate the inflammatory mode of the macrophages by causing reductions in iNOS and COX2 enzymes as well as IL-1β, IL-6, and TNF-α cytokine levels. The results of this study have shown the anti-inflammatory effects of this plant. Further studies regarding its therapeutic potential in inflammatory disorders are recommended.